A robust voltage control of dual active full bridge converter based on RBF neural network sliding mode control with reduced order modeling approach - Wang, Xiaosong; Wang, Dazhi; Sun, Guofeng; Ni, Yongliang; Song, Keling; Li, Yanming (Frontiers in Energy Research, 2023)
This paper presents a control method of dual active full bridge (DAB) DC/DC converter based on neural network Sliding mode control under the reduced order modeling method, which is used to enhance the output voltage regulation and improve the system robustness. Sliding mode control (SMC) is famous for its robustness and improving the dynamic performance of nonlinear systems.However, it includes drawbacks such as complex modeling, chattering, and decreased tracking performance. Therefore, through the method of reduced order modeling, the RBF neural network algorithm is selected to modify and design the traditional sliding mode variable structure controller, completing the design of neural network approximation terms and adaptive laws. The proposed reduced order modeling and RBF(Radial Basis Function Neural Network)-SMC scheme simplifies the DAB modeling process, completes the parameter approximation of the sliding mode controller, and eliminates the chattering problem. Firstly, through simulation and comparative analysis of commonly used modeling methods for DAB, a reduced order modeling method was adopted to simplify the design process. Then, by ingeniously designing the sliding mode surface and RBF control law, and using neural network to modify the Sliding mode control technology, the chattering problem, load disturbance and voltage fluctuation influence of the sliding mode controller are improved. The stability of the control method is proved by Lyapunov stability theory. Finally, the proposed RBF-SMC method is compared with PI linear control and classical SMC methods through simulation and experiments to verify the effectiveness of the proposed control method.